E-COUNSELING STMIK BANDUNG - Siti Yuliyanti; Muhamad Luthfir Rahman (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2020)
Counseling is the process of providing assistance through counseling interviews by counselors to individuals who are experiencing academic or non-academic problems. Counseling activities at STMIK Bandung have a problem, namely the unavailability of media specifically for conducting online counseling. it causes a lack of efficiency of students in consulting remotely. The development of E-Counseling is carried out by analyzing the counseling activities of STMIK Bandung and then designing which consists of object-oriented modeling, database structures, and application interfaces. The results of the development of E-Counseling STMIK Bandung support online counseling activities with increased efficiency and interactive which can help students to further increase their desire to consult with lecturers or academic staff as counselors. Keywords: E-Counseling, Counseling, students, problems, help